Los docentes y la evaluación - Emílio Tenti Fanfani (Universidade Católica Portuguesa, 2003)
Assessment is a pedagogic too! used systematically by the modem school, for two main reasons: the need to make an estimate of knowledge acquisition, and the need to award certification confirming the knowledge acquired. The standpoints and attitudes of teachers regarding assessment in a number of Latin American countries are presented and discussed in this article, which concludes that assessment is a problematic issue for the teachers.